The Effect Of Local Original Income, Public Consumption And Government Expenditure On Economic Growth In Indonesia: Panel Data Analysis 2014-2023 - Olos Wasahua; Sumaryoto; Karno (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Indonesia’s provincial economic development relies on strengthening regional fiscal capacity, sustaining domestic consumption, and improving the efficiency of productive government spending. This study analyzes the simultaneous impact of real per-capita Local Own-Source Revenue (PAD), household consumption, and regional government productive expenditure (GOV_EXP) on provincial economic growth across 34 provinces over 2014–2023, using a balanced dynamic panel regression with the Fixed Effect Model (FEM) as the main estimator. Prior to modeling, all independent variables achieved stationarity at the second difference, allowing stable panel estimation. Findings from FEM indicate that PAD (β = 0.082; t = 22.36; p = 0.000) provides the strongest positive growth effect, followed by household consumption (β = 0.043; t = 10.88; p = 0.000), and productive expenditure (β = 0.032; t = 7.46; p = 0.000), all statistically significant at α < 0.05. Results confirm that while productive public spending contributes to provincial GDP expansion, its growth elasticity remains more moderate relative to PAD and consumption, suggesting persistent regional fiscal efficiency challenges even in economically enabling sectors. The model also demonstrates that growth is demand-driven and regionally persistent, emphasizing that the synergy of fiscal autonomy and domestic purchasing momentum, rather than budget size alone, drives sustainable economic progress. Policy implications support digital fiscal transformation, optimized capital allocation, and consumption-supporting regional strategies to accelerate equitable and resilient provincial growth.